2009
DOI: 10.1111/j.1750-2659.2009.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic events underlying the changes in adamantane resistance among influenza A(H3N2) viruses during 2006–2008

Abstract: Background  Adamantanes resistance in H3N2 viruses has been increasing since 2000, and in 2005–2006 reached nearly 100% in most countries, with the circulation of the N‐lineage. In 2006–2007, however, a significant decrease in resistance was observed in many regions. Objectives  To explore potential links between adamantane resistance and the A(H3N2) viruses that circulated between 2006 and 2008. Methods  A total of 1451 Influenza A (H3N2) viruses collected globally in 2001–2008 were screened for the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Analysis of 95 H3N2 viruses collected during the following influenza season (2008-2009), using the RT-PCR/ESI-MS assay, revealed that they all retained the genomic prints CCDFAA or CCLFAA, which are characteristic of the D lineage, with no apparent evidence of major genetic changes based on this assay. These observations were consistent with the results obtained based on phylogenetic analyses [24].…”
Section: Rt-pcr/esi-ms Approach In Detection and Characterization Of Insupporting
confidence: 93%
See 1 more Smart Citation
“…Analysis of 95 H3N2 viruses collected during the following influenza season (2008-2009), using the RT-PCR/ESI-MS assay, revealed that they all retained the genomic prints CCDFAA or CCLFAA, which are characteristic of the D lineage, with no apparent evidence of major genetic changes based on this assay. These observations were consistent with the results obtained based on phylogenetic analyses [24].…”
Section: Rt-pcr/esi-ms Approach In Detection and Characterization Of Insupporting
confidence: 93%
“…in prior seasons, specifically the N-lineage [12,20]. Comparison of the RT-PCR/ESI-MS results with full-genome sequencing and phylogenetic data of the same 65 viruses showed that the 20 representative genomic prints identified clustered according to the four genetic lineages (A-D) determined by phylogenetic ana lysis [24].…”
Section: Rt-pcr/esi-ms Approach In Detection and Characterization Of Inmentioning
confidence: 95%
“…Indeed, large-scale sequencing of transmissible viruses isolated as early as 1918 showed that mutations to pore-lining residues are allowed only within the first turn of the transmembrane (TM) helix at positions 26, 27, and 31 (10). S31N has long been the predominant amantadine-resistant mutation in M2 (11)(12)(13)(14). It predominated in 98-100% of the transmissible amantadineresistant H1N1, H5N1, and H3N2 strains isolated from humans, birds, and swine in the past decade.…”
Section: M2-s31n Inhibitormentioning
confidence: 99%
“…1(A)]. S31N has long been the dominant amantadine-resistant mutation in M2, [46][47][48][49] accounting for 98-100%…”
Section: Natural and Artificial Sequence Variants Of M2mentioning
confidence: 99%